1996
DOI: 10.1046/j.1365-2958.1996.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical quorum‐sensing cascade in Pseudomonas aeruginosa links the transcriptional activators LasR and RhIR (VsmR) to expression of the stationary‐phase sigma factor RpoS

Abstract: In Pseudomonas aeruginosa, the production of many virulence factors and secondary metabolites is regulated in concert with cell density through quorum sensing. Two quorum-sensing regulons have been identified in which the LuxR homologues LasR and RhlR are activated by N-(3-oxododecanoyl)-L-homoserine lactone (OdDHL) and N-butanoyl-L-homoserine lactone (BHL) respectively. The lasR and rhlR genes are linked to the luxl homologues lasl and rhll, which are responsible for synthesis of OdDHL and BHL, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
589
6
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 642 publications
(619 citation statements)
references
References 39 publications
22
589
6
2
Order By: Relevance
“…The lack of signal effect can be most likely attributed to the experimental environment, which did not favor QS‐signaling: Resources are readily available in KB media (Friman et al., 2013) and the QS expression thus unlikely offered any additional benefits for the signaling bacteria. It is known that knocking out the las system will have downstream effects on the rhl system (Latifi et al., 1996), and as a result, it is often thought that the las mutants behave similarly as the rhl mutants. However, it has also been shown that las and rhl systems can be decoupled and that the interactions between different QS systems depend on the environmental conditions (Diggle et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of signal effect can be most likely attributed to the experimental environment, which did not favor QS‐signaling: Resources are readily available in KB media (Friman et al., 2013) and the QS expression thus unlikely offered any additional benefits for the signaling bacteria. It is known that knocking out the las system will have downstream effects on the rhl system (Latifi et al., 1996), and as a result, it is often thought that the las mutants behave similarly as the rhl mutants. However, it has also been shown that las and rhl systems can be decoupled and that the interactions between different QS systems depend on the environmental conditions (Diggle et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the signal diffusibility, AHLs must reach a critical environmental concentration before they cause changes in gene expression. It is common that the AHL synthase gene is among the genes activated, creating a positive feedback loop that results in increased production of signal (Engebrecht et al, 1983;Seed et al, 1995;Latifi et al, 1996;Duerkop et al, 2009;Stauff and Bassler, 2011). Thus, AHL signaling can coordinate population-wide changes in a celldensity-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…The opportunistic pathogen Pseudomonas aeruginosa produces two AHLs, N-(3-oxododecanoyl)-L L-homoserine lactone (3OC12HSL) and N-butanoyl-L L-homoserine lactone (C4HSL), which control production of extracellular virulence factors and biofilm formation [3][4][5][6][7]. Production of these AHLs is hierarchically regulated in which threshold levels of 3OC12HSL are required to activate the synthesis of C4HSL [6,7]. Considerable attention has been directed at developing anti-quorum-sensing agents as possible infection control therapeutics [8][9][10].…”
Section: Introductionmentioning
confidence: 99%